2020
DOI: 10.1093/restud/rdaa081
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Earnings Gap in the Gig Economy: Evidence from over a Million Rideshare Drivers

Abstract: The growth of the “gig” economy generates worker flexibility that, some have speculated, will favor women. We explore this by examining labor supply choices and earnings among more than a million rideshare drivers on Uber in the United States. We document a roughly 7% gender earnings gap amongst drivers. We show that this gap can be entirely attributed to three factors: experience on the platform (learning-by-doing), preferences and constraints over where to work (driven largely by where drivers live and, to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(129 citation statements)
references
References 45 publications
5
98
1
6
Order By: Relevance
“…A study analyzing more than a million drivers on the Uber platform in the US found a 7% earnings gap between men and women drivers (Cook et al 2018). This was attributed to gender differences in the experience of using the platform, preferences over where and when to work, and driving speed.…”
Section: Gendermentioning
confidence: 99%
“…A study analyzing more than a million drivers on the Uber platform in the US found a 7% earnings gap between men and women drivers (Cook et al 2018). This was attributed to gender differences in the experience of using the platform, preferences over where and when to work, and driving speed.…”
Section: Gendermentioning
confidence: 99%
“…This means that trust in intermediated care work is likely to be a valuable, yet volatile commodity distinct from other on-demand arrangements such as vendor-on-premises work or more transactional and impersonal platform-based service work such as cleaning, maintenance, driving or design (Flanagan, 2018;Ticona and Mateescu, 2018). Although the data do not allow for explicit comparisons of control strategies or worker participation profiles with platforms offering transactional or other types of intermediated work, nor with traditional care agencies, there is emerging evidence that the platform economy may be reproducing gendered features of labour markets and the gender pay gap that exists in the broader economy (Cook et al, 2018;McDonald et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is relatively little empirical evidence on gender wage gaps in OLMs. Notable exceptions are Chan and Wang (2017) and Cook et al (2018). Chan and Wang (2017) explore whether a worker's gender has an effect on the hiring decision of employers on OLMs.…”
Section: Figure 1 | Timing Of Competition For Contractsmentioning
confidence: 99%
“…It is in this respect that our results suggest that the higher winning probabilities of female online workers result from a rational (and not necessarily "biased") selection decision of employers. Our paper is also related to Cook et al (2018), who analyse whether there is a gender wage gap on Uber. They provide evidence for a 7% gender wage gap on Uber which is caused by differences in experience on the platform, preferences over working time and location, and preferences for driving speed.…”
Section: Figure 1 | Timing Of Competition For Contractsmentioning
confidence: 99%